Implementasi Manajemen Keuangan Perspektif Akuntansi pada Partai Demokrasi Indonesia Perjuangan (PDIP) Kabupaten Jember - Istiqomah, Lailatul; Ahmad, Arisona (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This research focuses on the implementation of financial management from an accounting perspective in the Indonesian Democratic Union party (PDIP) Jember Regency. The research design used is a qualitative method with a case study approach. The selection of informants used in this research was based on the snowball sampling method. The informants in this research were the secretary, treasurer, and party body administrators who were party members involved in financial management in PDIP Jember Regency. The result of the research show that financial management from an accounting perspective at PDIP Jember Regency has been implemented well. However, some have not implemented the principle of transparency as regulated in the Political Party Law.